Strategies to overcome the declining trend of young farmers: A comprehensive review of agricultural development issues - Uddin, Md Baha; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Agricultural production stands as the third-largest sector in Indonesia, yet the presence of young farmers, crucial for sustainable agricultural practices and food security, lags behind ideal proportions. Despite comprising 52% of the population, young people's engagement in farming falls short at approximately 30%. Methods: This paper delves into the underlying reasons behind this crisis, utilizing secondary data analysis from BPS Indonesia and employing documentary analysis methodology. Findings: The study reveals that the declining participation of Indonesian youth in agriculture is driven by intertwined structural, economic, and sociocultural barriers, necessitating a comprehensive, multi-stakeholder strategy to ensure generational renewal and long-term food security. Conclusion: The paper provides suggestions for further research to address this pressing issue and pave the way for a rejuvenated generation of farmers essential for Indonesia's agricultural future. Novelty/Originality of this article: This research offers a novel perspective by not only identifying challenges but also providing recommendations to revitalize youth engagement in agriculture, ensuring the sector’s long-term sustainability.